LSB Steganography to Embed Creator's Watermark in Batik Digital Arts - Muhammad Miftahul Amri; Mahamadaree Waeno; Muhammad Zain Musa (Engineering Science Letter, 2023)
This paper presents an implementation of Least Significant Bit (LSB) steganography to embed a hidden watermark in batik digital images. The goal of the technique is to provide a means of protecting the intellectual property of creators of batik digital arts while still allowing the images to be freely distributed and shared. The study demonstrates the effectiveness of the technique by showing that the embedded watermark is not visible to the human eye and does not significantly alter the quality of the image. The proposed technique uses the LSB method to embed a watermark in the binary data of the batik digital image. This method involves replacing the least significant bit of the image's pixel values with the bits of the watermark, thus altering the binary data of the image without causing noticeable changes in its visual appearance. The embedded watermark can only be detected by a decoding process, making it difficult to be removed or tampered with. The results of the study show that the implemented LSB steganography technique is successful in achieving its objective. The technique is able to effectively embed a hidden watermark in batik digital images without significantly altering the image quality or causing visual artifacts. This work highlights the potential of LSB steganography as a valuable tool for protecting the intellectual property of digital art creators, particularly in the field of batik images. Overall, this study contributes to the growing body of research on steganography and digital media protection. The successful implementation of the LSB steganography technique provides a promising approach for safeguarding the intellectual property of creators in the digital arts industry. Future research may explore other steganography techniques to address potential vulnerabilities and limitations of the LSB method.